A Feminist Stylistic Analysis of Virginia Woolf's A Room of One's Own - Suleman, Nazia; Zahra, Tabassum; Fatima, Mahnoor (Pakistan Journal of Humanities and Social Sciences, 2023)
This research paper explores the application of feminist stylistic analysis to Virginia Woolf's novel, A Room of One's Own. Using the theoretical framework of feminist literary criticism, this study examines the ways in which Woolf uses language and style to convey her feminist message. The research draws on close reading and textual analysis of selected passages from the novel, and employs feminist theories of language, gender, and power to interpret the meaning and significance of these stylistic choices. The findings of this study suggest that Woolf's use of language and style is crucial to her feminist message, and that it serves to challenge traditional gender roles and patriarchal power structures. Overall, this research contributes to our understanding of the intersection between feminist theory and literary analysis, and demonstrates the value of applying feminist stylistic analysis to works of literature.